2022
DOI: 10.25259/jhas_26_2021
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant antigenic expression in acute leukemia: Study from a tertiary care center in Southern India

Abstract: Objectives: Aberrant antigenic expression in acute leukaemia is an expression of antigens which is not normally associated with acute leukaemia of that specific lineage and does not fulfil the criteria for diagnosis of Mixed phenotype acute leukaemia (MPAL). This aberrant immunophenotype can be used for the assessment of measurable residual disease (MRD) and sometimes may predict certain genetic events. Material and Methods: This was a cross-sectional study conducted in a tertiary care centre in Southern Ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…In table [3], aberrant antigenic expression was more frequent in ALL than AML; T-ALL with aberrant expression was 66.6% of all T-ALL patients, while B-ALL with aberrant expression was 45.8% of all B-ALL patients, and AML with aberrant expression was 31.1% of all AML patients. Regarding aberrant expression in AML cases, cytoplasmic CD79a was the most frequently expressed antigen [16.7%], followed by CD10 and CD22 [5.6% and 1.1%, respectively], while expression of CD7 in AML cases was 12.2% of all AML cases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In table [3], aberrant antigenic expression was more frequent in ALL than AML; T-ALL with aberrant expression was 66.6% of all T-ALL patients, while B-ALL with aberrant expression was 45.8% of all B-ALL patients, and AML with aberrant expression was 31.1% of all AML patients. Regarding aberrant expression in AML cases, cytoplasmic CD79a was the most frequently expressed antigen [16.7%], followed by CD10 and CD22 [5.6% and 1.1%, respectively], while expression of CD7 in AML cases was 12.2% of all AML cases.…”
Section: Resultsmentioning
confidence: 99%
“…This aberrant leukemiaassociated immunophenotype [LAIP] can be used to monitor measurable residual disease [MRD]. Aberrant antigens in certain leukemias may indicate the presence of a genetic event or may affect the prognosis [3] . Flowcytometric immunophenotyping plays an important role in the identification of the lineage of AL along with the detection of aberrant antigens, which help in treatment monitoring and MRD analysis [4] .…”
Section: Introductionmentioning
confidence: 99%
“…Overall, we observed the expression of CD13 in 21.8% of the B‐ALL patients, CD33 in 19.7% of the B‐ALL patients, and CD117 in 4.7% of the B‐ALL patients. The authors from high‐income and low‐income countries reported the aberrant expression of myeloid marker expression including 10.5%–54.5% CD13, 2.6%–89% CD33, and 0%–26.2% CD117 38,39,60,62–75 . These differences in frequencies of expression of various myeloid markers might be attributed to the inherent genetic differences among ethnic subpopulations, technical factors such as lack of uniformity in using monoclonal antibody clone type, and differences in flow cytometry methodology, processing, and data analysis 74,76 .…”
Section: Discussionmentioning
confidence: 99%
“…Immunological characteristic of leukemic cells by flow cytometry helps in deciding about the different developmental stages and lineage of malignant cells. Aberrant expression of antigens means abnormal expression of cell specific lineage antigens which is not normally associated with acute leukemia of that specific lineage [8]. Different genetic defects can result in aberrant phenotype expression, that in turn is associated with unfavorable outcome.…”
Section: Introductionmentioning
confidence: 99%